1994
DOI: 10.1111/j.1432-1033.1994.tb20066.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Structure in Solution of a Wheat Lipid‐Transfer Protein from Multidimensional 1H‐NMR Data

Abstract: were used to build models of the three-dimensional structure of a non-specific wheat lipid-transfer protein (LTP) by using distance geometry, simulated annealing, energy minimization and molecular dynamics techniques. A first set of 881 distance constraints derived from NOE cross-peak intensities was used to generate 74 initial structures. One family of topological mirror images of the protein structure was eliminated by considering helical secondary-structure organization and steric requirements. Back calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 51 publications
7
131
0
Order By: Relevance
“…Concerning other structural elements, the 3D structures of RBI and wheat ns-LTP clearly reveal lower contents of -sheet or extended structures than those estimated from spectroscopic methods like IR or CD (Strobl et al, 1995;Gincel et al, 1994;Désormeaux et al, 1992;Alagiri & Singh, 1993). The three-dimensional structure of wheat ns-LTP does not reveal the existence of -sheets and shows only 7% -sheets in the case of RBI, while IR and CD predicted a -sheet content of 20-30% for both proteins.…”
Section: Infraredmentioning
confidence: 74%
“…Concerning other structural elements, the 3D structures of RBI and wheat ns-LTP clearly reveal lower contents of -sheet or extended structures than those estimated from spectroscopic methods like IR or CD (Strobl et al, 1995;Gincel et al, 1994;Désormeaux et al, 1992;Alagiri & Singh, 1993). The three-dimensional structure of wheat ns-LTP does not reveal the existence of -sheets and shows only 7% -sheets in the case of RBI, while IR and CD predicted a -sheet content of 20-30% for both proteins.…”
Section: Infraredmentioning
confidence: 74%
“…ClustalV multiple amino acid sequence alignment between the deduced sequence of the low-temperature responsive barley BLT4 proteins (White et al, 1994) and three non-specific lipid-transfer proteins (LTPs) with solved tertiary structures. NLTP_MAIZE, LTP from maize seedling (Shin et al, 1995); NLT1_HORVU, barley endosperm LTP (Heinemann et al, 1996); NLTA_WHEAT, LTP isolated from wheat seeds (Gincel et al, 1994). Sequence codes correspond to Swiss-Prot access codes.…”
Section: Resultsmentioning
confidence: 99%
“…and phosphatidylcholines have been shown to be efficiently transferred by LTPs (Kader, 1996a). X-ray crystallographic and 1 H-NMR analysis of several plant LTPs has demonstrated that they can accommodate only one acyl chain into their binding tunnel without major disturbance in the tertiary structure of the proteins (Gincel et al, 1994; Heinemann et al, 1996;Shin et al, 1995). Therefore, the second acyl chain attached to position 2 of glycerol was modelled on the surface of BLT4.9.…”
Section: Molecular Dynamics Simulation Aided Modelling Of Two Membranmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the three-dimensional crystal structures of maize nsLTP (mLTP) and the complex with palmitate (Shin et al, 1995) were reported, and so was the solution structure of wheat nsLTP (wLTP) (Gincel et al, 1995). These LTPs are four-helix proteins, and mLTP is shown to bind palmitate in an extended form in a hydrophobic cavity in the four-helix protein.…”
mentioning
confidence: 99%